A normative modeling approach to quantify white matter changes and predict functional outcomes in stroke patients - Su, Houming; Yan, Su; Zhu, Hongquan; Liu, Yufei; Zhang, Guiling; Peng, Xiaolong; Zhang, Shun; Li, Yuanhao; Zhu, Wenzhen (Frontiers in Neuroscience, 2024)
Objectives: The diverse nature of stroke necessitates individualized assessment, presenting challenges to case-control neuroimaging studies. The normative model, measuring deviations from a normal distribution, provides a solution. We aim to evaluate stroke-induced white matter microstructural abnormalities at group and individual levels and identify potential prognostic biomarkers.Methods: Forty-six basal ganglia stroke patients and 46 healthy controls were recruited.Diffusion-weighted imaging and clinical assessment were performed within 7 days after stroke.We used automated fiber quantification to characterize intergroup alterations of segmental diffusion properties along 20 fiber tracts. Then each patient was compared to normative reference (46 healthy participants) by Mahalanobis distance tractometry for 7 significant fiber 2 tracts. Mahalanobis distance-based deviation loads (MaDDLs) and fused MaDDLmulti were extracted to quantify individual deviations. We also conducted correlation and logistic regression analyses to explore relationships between MaDDL metrics and functional outcomes.: Disrupted microstructural integrity was observed across the left corticospinal tract, bilateral inferior fronto-occipital fasciculus, left inferior longitudinal fasciculus, bilateral thalamic radiation, and right uncinate fasciculus. The correlation coefficients between MaDDL metrics and initial functional impairment ranged from 0.364 to 0.618 (P<0.05), with the highest being MaDDLmulti. Furthermore, MaDDLmulti demonstrated a significant enhancement in predictive efficacy compared to MaDDL (integrated discrimination improvement [IDI] = 9.62%, P = 0.005) and FA (IDI = 34.04%, P < 0.001) of the left corticospinal tract. Conclusions: MaDDLmulti allows for assessing behavioral disorders and predicting prognosis, offering significant implications for personalized clinical decision-making and stroke recovery.Importantly, our method demonstrates prospects for widespread application in heterogeneous neurological diseases.